{[(8×4+3)÷7+(3+15÷5)•3]•2-(19-7)÷6}•2+12=
Soluções para a tarefa
Respondido por
1
Resposta:
{ [ ( 8 × 4 + 3 ) ÷ 7 + ( 3 + 15 ÷ 5 ) • 3 ] • 2 - ( 19 - 7 )÷6}•2+12=
{ [ ( 32 + 3 ) ÷ 7 + ( 3 + 3 ) • 3 ] • 2 - 12 ÷ 6 } • 2 + 12=
{ [ 35 ÷ 7 + 6 • 3 ] • 2 - 12 ÷ 6 } • 2 + 12=
{ [ 5 + 6 • 3 ] • 2 - 12 ÷ 6 } • 2 + 12=
{ [ 5 + 18 ] • 2 - 12 ÷ 6 } • 2 + 12=
{ 23 • 2 - 12 ÷ 6 } • 2 + 12=
{ 46 - 12 ÷ 6} • 2 + 12=
{ 46 - 2 } • 2 + 12=
44 • 2 + 12=
88 + 12=
100#
Perguntas interessantes
Português,
7 meses atrás
Português,
7 meses atrás
Matemática,
7 meses atrás
Biologia,
8 meses atrás
Matemática,
8 meses atrás
Matemática,
1 ano atrás